Normal Bone Marrow and Non-neoplastic Systemic Hematopoietic Disorders in the Adult - Tyler, Philippa Anne; Rajakulasingam, Ramanan; Saifuddin, Asif (Seminars in Musculoskeletal Radiology, 2023)
This article provides an overview of the imaging appearances of normal adult bone marrow with an emphasis on magnetic resonance imaging. We also review the cellular processes and imaging features of normal developmental yellow-to-red marrow conversion and compensatory physiologic or pathologic red marrow reconversion. Key imaging features that differentiate between normal adult marrow, normal variants, non-neoplastic hematopoietic disorders, and malignant marrow disease are discussed, as well as posttreatment changes.
Keywords: marrow reconversion; magnetic resonance imaging; hematopoietic; red and yellow bone marrow